Mencari Penyebab Penurunan Minat Calon Mahasiswa D3 Akuntansi: Faktor Internal dan Eksternal - Sukiyaningsih, Tri Wahyuni; Hasanah, Ade Nahdiatul; Juwita, Salsadilah (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This research aims to find out the cause of the decline in interest in the D3 Accounting study program at Serang Raya University. In recent years, there has been a decline ini interest in this study program. Researchers are looking for any casual factors that might cause this number students. The causal factors that will be studied are internal and external factors in the research object, namely vocational and hing school students who have studied accounting at least at the journaling stage. The object this research was 100 respondents